2007
DOI: 10.1111/j.1365-2311.2007.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity of ambrosia and bark beetles (Col., Curculionidae: Scolytinae and Platypodinae) in a New Guinea rainforest

Abstract: Abstract. 1. Bark and ambrosia beetles are crucial for woody biomass decomposition in tropical forests worldwide. Despite that, quantitative data on their host specificity are scarce.2. Bark and ambrosia beetles (Scolytinae and Platypodinae) were reared from 13 species of tropical trees representing 11 families from all major lineages of dicotyledonous plants. Standardised samples of beetle-infested twigs, branches, trunks, and roots were taken from three individuals of each tree species growing in a lowland t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 42 publications
(57 reference statements)
3
80
0
5
Order By: Relevance
“…Contrary to most Xavier Martini and Marc A. Hughes contributed equally to this work. ambrosia beetles that attack weakened, damaged or recently dead trees (Hulcr et al 2007;Lindgren 1990), X. glabratus can attack live and apparently healthy trees within its introduced range in the US Mayfield et al 2008). Additionally, X. glabratus is not attracted to ethanol (Hanula and Sullivan 2008;Johnson et al 2014), a semiochemical indicative of tree stress and decay (Kelsey et al 2014;Kimmerer and Kozlowski 1982) that is used as an attractant for monitoring of various ambrosia beetles and wood borers of the Xyleborini tribe (Miller and Rabaglia 2009;Montgomery and Wargo 1983;Ranger et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Contrary to most Xavier Martini and Marc A. Hughes contributed equally to this work. ambrosia beetles that attack weakened, damaged or recently dead trees (Hulcr et al 2007;Lindgren 1990), X. glabratus can attack live and apparently healthy trees within its introduced range in the US Mayfield et al 2008). Additionally, X. glabratus is not attracted to ethanol (Hanula and Sullivan 2008;Johnson et al 2014), a semiochemical indicative of tree stress and decay (Kelsey et al 2014;Kimmerer and Kozlowski 1982) that is used as an attractant for monitoring of various ambrosia beetles and wood borers of the Xyleborini tribe (Miller and Rabaglia 2009;Montgomery and Wargo 1983;Ranger et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Evidence that evolved defenses play a role in mediating plant-herbivore interactions (Agrawal 2005) has supported the view that a phylogenetic context is needed to test predictions about trophic relationships (Lamarre et al 2012). The distribution of herbivore dietary preferences with respect to plant community phylogeny has further suggested that many tropical insect species are clade specialists (Tavakilian et al 1997, Berkov and Tavakilian 1999, Novotny et al 2002, 2004, 2010, Novotny and Basset 2005, Odegaard et al 2005, Weiblen et al 2006, Dyer et al 2007, Hulcr et al 2007). However, it is unclear what effect the phylogenetic distribution of plant traits might have on overall patterns of herbivore abundance at the community level.…”
Section: Introductionmentioning
confidence: 99%
“…These species should not be included in the host selection analyses as their apparent narrow host range can be artifact (Novotny and Basset 2000;Hulcr et al 2007). Niche overlap in host resource utilization for 12 most abundant sucking louse species (comprised of 92.13% of total louse species) on 18 species of small mammalian hosts (regarded as 18 series of host resources for the lice) was evaluated using Pianka index (Pianka 1973):…”
Section: Methodsmentioning
confidence: 99%